Implementation of Higher Order Thinking Skills (HOTS) in Teaching Reading in the Era Society 5.0 - Siti Qoriah; Muhammad Sofian Hadi; Lidyatul Izzah (Tarbiatuna: Journal of Islamic Education Studies, 2023)
The purpose of this study is to determine how effective HOTS instruction has improved the reading abilities of students in class VIII at MTsN 1 South Tangerang. The descriptive approach was employed in this study, and the data were gathered through test-taking, teacher and student interviews, as well as observation of class activities. The results also indicate that the teacher frequently employed a technique similar to HOTS, such as an excellent game, in the classroom to stimulate students' critical thinking. The data analysis leads to the conclusion that HOTS is appropriate for use in teaching reading to junior high school students. Keywords: Reading, HOTS, Society 5.0 References (2010-2022)